Local anaesthetic toxicity during an awake tracheal intubation course. Issue 1 (2nd March 2020) - Pearson, F.; Chiam, P.
Summary: We report a case of local anaesthetic toxicity in an anaesthetic trainee participating as a subject for an awake tracheal intubation training course. The trainee experienced symptoms of toxicity despite the dose of lidocaine administered being less than the maximum safe dose recommended for airway topicalisation. We argue this highlights the variability in absorption of local anaesthetic and the importance of safety during awake tracheal intubation training courses. It is essential to use the minimum safe dose of local anaesthetic required during topicalisation for awake tracheal intubation. We have now made it our course policy that participants cannot undergo awake tracheal intubation less than 2 weeks following a period of coryzal illness. We recommend that operators remain vigilant for signs of local anaesthetic toxicity when undertaking this procedure and adhere to newly published Difficult Airway Society awake tracheal intubation guidelines.